A comparison between the original and Tablet-based Symbol Digit Modalities Test in patients with schizophrenia: Test-retest agreement, random measurement error, practice effect, and ecological validity. (February 2018) - Tang, Shih-Fen; Chen, I.-Hui; Chiang, Hsin-Yu; Wu, Chien-Te; Hsueh, I.-Ping; Yu, Wan-Hui; Hsieh, Ching-Lin
Abstract: We aimed to compare the test-retest agreement, random measurement error, practice effect, and ecological validity of the original and Tablet-based Symbol Digit Modalities Test (T-SDMT) over five serial assessments, and to examine the concurrent validity of the T-SDMT in patients with schizophrenia. Sixty patients with chronic schizophrenia completed five serial assessments (one week apart) of the SDMT and T-SDMT and one assessment of the Activities of Daily Living Rating Scale III at the first time point. Both measures showed high test-retest agreement, similar levels of random measurement error over five serial assessments. Moreover, the practice effects of the two measures did not reach a plateau phase after five serial assessments in young and middle-aged participants. Nevertheless, only the practice effect of the T-SDMT became trivial after the first assessment. Like the SDMT, the T-SDMT had good ecological validity. The T-SDMT also had good concurrent validity with the SDMT. In addition, only the T-SDMT had discriminative validity to discriminate processing speed in young and middle-aged participants. Compared to the SDMT, the T-SDMT had overall slightly better psychometric properties, so it can be an alternative measure to the SDMT for assessing processing speed in patients with schizophrenia. Highlights: The Tablet-based Symbol Digit Modalities Test (T-SDMT) can substitute for the SDMT. The practice effect of the T-SDMT becomes trivial after the first assessment. More practice with using the tablet computer is needed before the testing of T-SDMT.